Reaksi Pasar Sebelum dan Sesudah Stock Split - Gladys Rilana Suryadi; Ni Putu Santi Suryantini (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2024)
Profit is the goal of investing in the capital market. Based on market efficiency theory, market share prices in the semi-strong form reflect all information regarding past prices and all information published by related companies, so investors need information to reduce uncertainty. A stock split is an activity of splitting a number of shares into a larger number of shares using a proportionally lower nominal value per share. This research is research with a quantitative approach in the event study category. In this research, there are 31 samples of companies listed on the Indonesia Stock Exchange and carrying out stock splits in the 2020-2023 period. The research data tested is secondary data accessed via the Indonesia Stock Exchange website. The aim of this research is to find out whether there are significant differences in stock trading volume and abnormal returns before and after the stock split. The results of this study show that there is no significant difference in stock trading volume and abnormal returns before and after the stock split.